Optimizing the Use of QR Codes in Web-Based Attendance Information Systems During the Covid-19 Pandemic (Case Study: KONI Salatiga City) - Deni Dwi Saputra; Andeka Rocky Tanaamah (Institute of Computer Science (IOCS), 2021)
The Covid-19 pandemic that occurred in mid-March 2020 caused the situation to change completely, and companies and agencies began implementing physical distancing and work from home. KONI Salatiga City is one of the agencies affected by the Covid-19 pandemic. One of the sectors of the Salatiga City KONI that was affected was the attendance section. Attendance data retrieval conducted at KONI Salatiga City is still done manually by signing in the attendance book. Therefore, by utilizing the right information system technology, it can solve this problem. Namely by building a QR Code-based attendance information system. The method used in building an attendance information system is to use the waterfall method. This method is very effective in conducting system design because it is carried out systematically.